Calculation of Equilibrium Concentrations of Calcium Ions for Calcium Bicarbonate Removal from Water Solution with Ammonium Hydroxide; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Zhuravkov S. P. Sergey Petrovich; Kataev M. Yu. Mikhail Yurievich; Malanova N. V. Natalya Viktorovna; Marinin S. A. (Chemical Engineering and Technology, 2016)
Title screen